2015
DOI: 10.1007/s10725-015-0102-6
|View full text |Cite
|
Sign up to set email alerts
|

The exogenous application of spermidine alleviates photosynthetic inhibition and membrane lipid peroxidation under low-light stress in tomato (Lycopersicon esculentum Mill.) seedlings

Abstract: The effects of three concentrations (0.001, 0.01, and 0.1 mg/L) of exogenous spermidine (Spd) on the O 2 Á-production rate, malondialdehyde (MDA) content, antioxidant enzyme activities, leaf photosynthesis, chlorophyll content, chlorophyll fluorescence, and light response curve parameters were investigated in the seedlings of two tomato cultivars: low-light-stress-tolerant 'Zhongza 9' and sensitive 'Zhongshu 6'. Low-light stress of 150 lmol m -2 s -1 resulted in an increase in the O 2 Á-production rate, MDA co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…In this study, compared with no shading, the ch rophyll and carotenoid contents in shaded leaves increased significantly at the later sta while the chl a/b ratio decreased, which was consistent with the reports of strawberry a rice [2,29]. The results indicated that shaded jujube leaves obtained higher light energy increasing photosynthetic pigment contents and meanwhile improved photosynthe phosphorylation activity by reducing the chl a/b ratio [30,31]. However, the decrease specific leaf weight in jujube leaves indicated that the enhanced capacity for light captu did not compensate for the reduction in leaf photosynthesis caused by shading, wh was similar to results from studies of black currant, grape, and cigar tobacco leaves [3 34].…”
Section: Shading Increased Photosynthetic Pigment Contents Of Leaves ...supporting
confidence: 91%
See 1 more Smart Citation
“…In this study, compared with no shading, the ch rophyll and carotenoid contents in shaded leaves increased significantly at the later sta while the chl a/b ratio decreased, which was consistent with the reports of strawberry a rice [2,29]. The results indicated that shaded jujube leaves obtained higher light energy increasing photosynthetic pigment contents and meanwhile improved photosynthe phosphorylation activity by reducing the chl a/b ratio [30,31]. However, the decrease specific leaf weight in jujube leaves indicated that the enhanced capacity for light captu did not compensate for the reduction in leaf photosynthesis caused by shading, wh was similar to results from studies of black currant, grape, and cigar tobacco leaves [3 34].…”
Section: Shading Increased Photosynthetic Pigment Contents Of Leaves ...supporting
confidence: 91%
“…The chlorophyll contents increased first and then decreased, while carotenoid content gradually increased during leaf development (Figure 1). The contents of chl a, chl b, and total chl were significantly higher with MS and SS treatment for 31…”
Section: Dynamic Changes Of Photosynthetic Pigments and Specific Leaf...mentioning
confidence: 91%
“…Generally, higher levels of light than are necessary for crop growth cause photostress, leading to photoinhibition, which reduces growth and decreases the efficiency of the quantum yield in reaction centers (RCs) of photosystem II (PSII) ( Szymańska et al, 2017 ; Lima-Melo et al, 2019 ). In contrast, low light conditions during the cultivation of field crops and protected horticultural crops have been reported to not only reduce photosynthesis and plant growth, but also cause yield loss and quality degradation ( Yu et al, 2016 ; Gao et al, 2017 ; Zhu et al, 2017 ; Lu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This result was unexpected considering that photooxidative stress is usually associated to conditions of excessive light intensities (Li et al, 2018;Roach & Krieger-Liszkay, 2019). However, several works have shown that short-term low light can also induce oxidative stress, as measured by different indicators (Yu et al, 2016;Li et al, 2017;Zhu et al, 2017), although the molecular mechanisms involved in this specific condition is not as well understood as for high light. Our data also show that in vitro leaves displayed much higher ROS accumulation than ex vitro leaves for all treatments, and this response was correlated with progressive decrease in SOD, CAT and APX activities.…”
Section: Discussionmentioning
confidence: 95%